2017
DOI: 10.1371/journal.ppat.1006693
|View full text |Cite
|
Sign up to set email alerts
|

iRhom2 is essential for innate immunity to RNA virus by antagonizing ER- and mitochondria-associated degradation of VISA

Abstract: VISA (also known as MAVS, IPS-1 and Cardif) is an essential adaptor protein in innate immune response to RNA virus. The protein level of VISA is delicately regulated before and after viral infection to ensure the optimal activation and timely termination of innate antiviral response. It has been reported that several E3 ubiquitin ligases can mediate the degradation of VISA, but how the stability of VISA is maintained before and after viral infection remains enigmatic. In this study, we found that the ER-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…These include OTUD4, PCBP2, RNF5, Tetherin, NS1 of Duck Tembusu Virus, iRhom2, ECSIT and GP73. 27,29,34,36,[52][53][54] The TM domain of MAVS is also crucial for its oligomerization after viral infection. 11,55 Interestingly, the truncated MAVS(aa361-540) used in this study is sufficient to activate ISRE or NF-κB in reporter assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include OTUD4, PCBP2, RNF5, Tetherin, NS1 of Duck Tembusu Virus, iRhom2, ECSIT and GP73. 27,29,34,36,[52][53][54] The TM domain of MAVS is also crucial for its oligomerization after viral infection. 11,55 Interestingly, the truncated MAVS(aa361-540) used in this study is sufficient to activate ISRE or NF-κB in reporter assays.…”
Section: Discussionmentioning
confidence: 99%
“…34 More recently, it has been reported that OTUD1 induces the upregulation of Smurf1 to promote ubiquitination and proteasomal degradation of MAVS, 35 whereas iRhom2 promotes ubiquitination and degradation of RNF5 and MARCH5 to antagonize MAVS degradation. 36 However, the process whereby MAVS is deubiquitinated is unclear and whether and how its deubiquitination might regulate the innate antiviral responses remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…HFFs were provided by Dr. Min-Hua Luo (Wuhan Institute of Virology, CAS). SeV (Cantell strain), EMCV (BJC3 Strain) and VSV (Indiana Strain) were previously described [28,30].…”
Section: Reagents Antibodies Cells and Virusesmentioning
confidence: 99%
“…In agreement with findings in Sting ‐deficient mice, iRhom2 ‐deficient mice are significantly less resistant to HSV‐1 infection. In a follow‐up study, the authors also invoke a role for iRhom2 in innate immune responses to the RNA virus VSV by mediating the protein stability of the central adaptor mitochondrial antiviral signaling protein (MAVS) . By mediating the auto‐ubiquitination and degradation of the E3 ubiquitin ligase ring finger protein (RNF) 5, which then prevents the assembly of MAVS‐RNF5 complexes, iRhom2 antagonizes ER‐associated degradation of MAVS.…”
Section: Biological Functions Of Irhomsmentioning
confidence: 99%
“…Similar to rhomboids, iRhom2 and possibly iRhom1 also require transmembrane interactions with their interacting binding partners for their biological functions . Targeting membrane protein interactions offer significant challenges for designing anti‐TMD directed therapeutics.…”
Section: Irhoms As Targets For Drug Developmentmentioning
confidence: 99%